Prevalence of talon cusps in a Portuguese population: Forensic identification significance of a rare trait - Ricardo Jorge Simões; Hugo F.V. Cardoso; Inês Morais Caldas (Wolters Kluwer Medknow Publications, 2014)
Background: Dental techniques are frequently used in human identification; some of those include comparative analyses of dental features that, being rare or unique to an individual, can establish a positive identification. The usefulness of each feature depends on its population, frequency, and uniqueness. The aim of this study was to determine the prevalence of talon cusps in a Portuguese population. Materials and Methods: A prospective study was performed. Three hundred and two patients were studied, and talon cusps presence was assessed. Statistical tests were carried out using Statistical Package for the Social Sciences (SPSS) 17 software (SPSS Inc., Chicago, IL, USA). Statistical analysis relied primarily on descriptive statistics and crosstabs, with Chi-square analysis. Results: Results showed that talon cusps were observed in only 6.3% of patients. The maxillary lateral incisors were the most common teeth showing this feature (82.1% of all teeth). Conclusion: It can be concluded that talon cusps are an uncommon trait in these Portuguese population, and therefore, it is a feature that can be potentially very useful in forensic human identification, when antemortem dental records are available.